Anthropometric determinants of lung function in apparently healthy individuals - Michael O. Ogunlana; Olufemi O. Oyewole; Adetutu I. Lateef; Ayomikun F. Ayodeji (AOSIS, 2021)
Background: Forced vital capacity (FVC) and peak expiratory flow rate (PEFR) are used to assess and monitor the management of lung pathology. Objectives: Our study documented spirometry reference values for apparently healthy Nigerians and developed predictive equations for pulmonary function. Method: A cross-sectional survey involving healthy adult Nigerians included anthropometric measurements of weight, height, waist, hip circumference (HC), sagittal abdominal diameter (SAD) and percentage body fat. Anthropometric indices (body mass index [BMI] and waist-to-hip ratio [WHR]) were estimated and pulmonary function tests (FVC, forced expiratory volume in 1 s [FEV1], PEFR, FEV1/FVC ratio) measured. The association amongst selected anthropometric and socio-demographic variables and pulmonary function test parameters were established using t-tests and Pearson's product moment correlation tests. The predictors of pulmonary function were established using stepwise multiple linear regression models. Results: Four hundred and forty-four adults (156 [35.1%] men) were included, mean age 37.3 ± 8.25 (range 22-25) years. Male participants had significantly higher lung volumes than females (p 0.05). Age, height, weight and percentage body fat had significant low correlations with lung function test parameters (p 0.05). Fat-free mass (FFM), fat mass (FM), SAD, height and age of participants were main predictors of FVC and FEV1 (R2 = 0.43 and 0.41, respectively). Fat-free mass and SAD were main predictors of PEFR (R2 = 0.53). Sagittal abdominal diameter and age were main predictors of FEV1/FVC ratio (R2 = 0.34). Conclusion: Fat-free mass, FM, height, age and SAD are important determinants of lung volumes and key variables for predictive equations of pulmonary function. Clinical implications: An accurate documentation of pulmonary function values for apparently healthy Nigerian adults may be useful in identifying deviations from normative values thereby giving an index of suspicion for the diagnosis of pulmonary dysfunction.